Activation of protease‐activated receptor‐2 disrupts vaginal epithelial barrier function. (19th August 2014) - Li, Yan; Feng, Chong; Wei, Xing; Zhang, Jiyuan; Zan, Ronghua; Zheng, Guizhi; Yang, Xiaoying; Zhai, Jianjun
Abstract The epithelial cell barrier function is a critical factor in the maintenance of the homeostasis of the vaginal mucosa. This study elucidates one of the mast cell‐derived chemical mediators, tryptase, on compromising the vaginal epithelial barrier function. The results showed that human vaginal cell line, VK2, express PAR2. Activation of PAR2 increases the expression of ADAM10 in VK2 cells, interferes with the endosome/lysosome fusion, and compromises the epithelial barrier function. We conclude that the activation of PAR2 on VK2 cells increases the expression of ADAM10, and compromises the VK2 monolayer barrier function.